2017
DOI: 10.1016/j.bandl.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A common variant of the CNTNAP2 gene is associated with structural variation in the left superior occipital gyrus

Abstract: a b s t r a c tThe CNTNAP2 gene encodes a cell-adhesion molecule that influences the properties of neural networks and the morphology and density of neurons and glial cells. Previous studies have shown association of CNTNAP2 variants with language-related phenotypes in health and disease. Here, we report associations of a common CNTNAP2 polymorphism (rs7794745) with variation in grey matter in a region in the dorsal visual stream. We tried to replicate an earlier study on 314 subjects by Tan et al. (2010), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…With respect to brain structure, two studies have identified regional reductions in gray matter volume associated with the risk allele on rs7794745 primarily affecting occipital, fusiform, and cerebellar regions (Tan, Doke, Ashburner, Wood, & Frackowiak, ; Uddén, Snijders, Fisher, & Hagoort, ). Additionally, altered white matter structure associated with CNTNAP2 has been reported in fronto‐occipital and thalamic tracts (Tan et al, ) as well as midbrain tracts that facilitate communication among the cortex, cerebellum, and other central nervous system structures (Skeide et al, ).…”
Section: Developmental Language Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to brain structure, two studies have identified regional reductions in gray matter volume associated with the risk allele on rs7794745 primarily affecting occipital, fusiform, and cerebellar regions (Tan, Doke, Ashburner, Wood, & Frackowiak, ; Uddén, Snijders, Fisher, & Hagoort, ). Additionally, altered white matter structure associated with CNTNAP2 has been reported in fronto‐occipital and thalamic tracts (Tan et al, ) as well as midbrain tracts that facilitate communication among the cortex, cerebellum, and other central nervous system structures (Skeide et al, ).…”
Section: Developmental Language Disordermentioning
confidence: 99%
“…Further, these authors observed an interaction between lateralization of function during voice processing (forward and reversed speech), rs7794745 genotype, and handedness, suggesting a complex influence of this SNP on voice processing networks in relation to handedness and lateralization. 6 With respect to brain structure, two studies have identified regional reductions in gray matter volume associated with the risk allele on rs7794745 primarily affecting occipital, fusiform, and cerebellar regions (Tan, Doke, Ashburner, Wood, & Frackowiak, 2010;Uddén, Snijders, Fisher, & Hagoort, 2017). Additionally, altered white matter structure associated with CNTNAP2 has been reported in fronto-occipital and thalamic tracts (Tan et al, 2010) as well as midbrain tracts that facilitate communication among the cortex, cerebellum, and other central nervous system structures (Skeide et al, 2016).…”
Section: Cntnap2mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies have supported the notion that these common variants play a role in psychiatric disorders. SNP rs2710102 has been implicated in brain connectivity in healthy individuals [16, 18, 19], and rs7794745 was implicated in audio-visual speech perception [69], voice-specific brain function [22], and was associated with reduced grey matter volume in left superior occipital gyrus [20, 21]. These studies focused principally on language tasks in general population, given the reported suggestive implications of CNTNAP2 in language impairment traits of ASD or language-related phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in subsequent studies, rs2710102 was implicated in early language acquisition in the general population [15], and showed functional effects on brain activation in neuroimaging studies [16-19]. Furthermore, genotypes at rs7794745 were associated with reduced grey matter volume in the left superior occipital gyrus in two independent studies [20, 21], and alleles of this SNP were reported to affect voice-specific brain function [22]. Genetic associations with ASD for these, and several other SNPs in CNTNAP2 , have been reported in a number of studies [23-28].…”
Section: Introductionmentioning
confidence: 99%